2022
DOI: 10.3389/fphar.2022.979474
|View full text |Cite
|
Sign up to set email alerts
|

Circulating galectin-3 promotes tumor-endothelium-adhesion by upregulating ICAM-1 in endothelium-derived extracellular vesicles

Abstract: The adhesion of tumor cells to vascular endothelial cells is an important process of tumor metastasis. Studies have shown that tumor could educate vascular endothelial cells to promote tumor metastasis through many ways. However, the effect of tumor cells on the functions of vascular endothelial cells-derived extracellular vesicles (H-EVs) and the mechanisms underlying their effects in tumor-endothelium adhesion in metastasis remain mysterious. In this study, we found that H-EVs promoted the adhesion of triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although the importance of the glycolytic pathway in maintaining EC function and normalizing TECs is well established, only the PFKBF3 glycolytic enzyme has been shown to regulate inter-EC connections by some unknown mechanism [ 63 ]. In addition to glycolytic enzymes, extracellular vesicles (H-EVs) have recently been found to promote adhesion of cancer cells to endothelial cells in triple-negative breast cancer, and Circulating galectin-3(cirGal-3) enhances this proadhesive effect by a mechanism that may be related to cirGal-3-induced increased expression of ICAM-1, leading to upregulation of glycolysis in endothelial cells [ 66 ]. This special function of PKM2 in maintaining the integrity of the endothelial barrier during migration and thus reducing tumor metastasis provides a new therapeutic strategy for antitumor treatment, namely, targeting PKM2 to inhibit tumor metastasis [ 67 ].…”
Section: Glucose Metabolism Characteristics Of Tumor Endothelial Cellsmentioning
confidence: 99%
“…Although the importance of the glycolytic pathway in maintaining EC function and normalizing TECs is well established, only the PFKBF3 glycolytic enzyme has been shown to regulate inter-EC connections by some unknown mechanism [ 63 ]. In addition to glycolytic enzymes, extracellular vesicles (H-EVs) have recently been found to promote adhesion of cancer cells to endothelial cells in triple-negative breast cancer, and Circulating galectin-3(cirGal-3) enhances this proadhesive effect by a mechanism that may be related to cirGal-3-induced increased expression of ICAM-1, leading to upregulation of glycolysis in endothelial cells [ 66 ]. This special function of PKM2 in maintaining the integrity of the endothelial barrier during migration and thus reducing tumor metastasis provides a new therapeutic strategy for antitumor treatment, namely, targeting PKM2 to inhibit tumor metastasis [ 67 ].…”
Section: Glucose Metabolism Characteristics Of Tumor Endothelial Cellsmentioning
confidence: 99%
“…Wang et al have recently found that human EC-derived extracellular vesicles (H-EVs) mediate the adhesion of breast cancer cells to human umbilical vein endothelial cells (HUVECs), an effect that is enhanced by circulating Gal-3 (101). Mechanistically, their data show that Gal-3 induces ICAM-1 upregulation in HUVECs, which is transferred to cancer cells via H-Evs, promoting CTC-EC adhesion (101). Interestingly, Zhang et al have identified Gal-3 as a potential mediator of integrin avb1 export into EVs derived from breast cancer cells, promoting their communication with other cell types, including ECs (102).…”
Section: Gal-3-mediated Cancer Cell Adhesion To Vascular Endotheliummentioning
confidence: 99%
“…Furthermore, EVs originated from vascular endothelial cells were found to induce the adhesion of triple-negative breast cancer cells to endothelial cells, and this process could be enhanced by cirGal-3. Further mechanistic exploration revealed that the enhanced glycolysis of endothelial cells induced by cirGal-3 could increase ICAM-1 expression; and EVs-dependent delivery of cirGal-3 to triplenegative breast cancer cells (MDA-MB-231) increased adhesion between the two cell types, ultimately leading to brain metastases of breast cancer (68). Moreover, Sirkisoon et al have revealed that miR-1290-containing EVs derived from breast cancer activate astrocytes in brain TME via the FOXA2-CNTF axis.…”
Section: Tumor-derived Evs Promote Metastasismentioning
confidence: 99%